Prispevek k obvladovanju neuravnoteženosti krempljastih polov alternatorjev - Nastran, Miha (Strojniški vestnik, 2002)
The claw pole still represents the largest and the heaviest part of an alternator's rotor: and it is expected that alternators will continue to be used for electric power generation in motor vehicles for at least a decade. Due to the high speeds of the rotor during operation its mass centricity is very important for the service life of the bearings, low noise and smooth running. This paper presents the production of claw poles using cold-forming technology, and a focus on reducing the electricity. Achieving this aim will mean a step towards shortening the time needed for automated balancing. We start with the problem of production and principle of balancing, this is followed by an experimental analysis of current production and a FEM analysis, which helps to describe the reasons why unbalance occurs. Emphasis is placed on work towards improving the tooling system for achieving well-balanced claw poles after cold forming.
Keywords: rotorji alternatorjev; uravnoteženost mas; sistemi orodni; metode numerične; alternatorji; rotor; preoblikovanje; uravnoteženje; numerične metode